Mode of Action Temu Kunci (Kaempferia pandurata) Essential Oil on E. coli K1.1 Cell Determined by Leakage of Material Cell and Salt Tolerance Assays - MIKSUSANTI MIKSUSANTI; BETTY SRI LAKSMI JENIE; BAMBANG PONTJO PRIOSOERYANTO; RIZAL SYARIEF; GATOT TRIMULYADI REKSO (HAYATI Journal of Biosciences, 2008)
The essential oil of Kaempferia pandurata consist of terpen and oxygenated terpen that exhibits broad-spectrum antimicrobial activity. It’s mode of action against the gram-negative bacterium E. coli K1.1 has been investigated using a range of treatments. The mode action of the essential oil were analyzed by it’s ability to leakage E. coli K1.1 cell, to change permeability of the cell, and to alter salt tolerance of the cell. Ion leakage from the cell were analyzed by atomic absorption spectrophotometer. Salt tolerance assays was conducted by investigating the ability of E. coli K1.1 treated with temu kunci essential oil to grow on NA supplemented with NaCl. Protein and acid nucleic leakage were analyzed by UV spectrophotometer. There were inorganic compound leakage (potassium, calcium ion) and organic compound leakage (nucleic acid, protein) from cytoplasmic membrane, after exposing this organism to essential oil of Kaempferia pandurata. The more concentration of oil added, the more leakage was observed due to the loss of absorbing material such as nucleic acid (260 nm) and protein (280 nm), the loss of potassium and calcium ion, and loss of the salt tolerance of E. coli K1.1. Key words: essential oil, E. coli K1.1, leakage, salt tolerance assay